Identification of Resistivity Distributions in Dielectric Layers by Measurement Model Analysis of Impedance Spectroscopy. (20th November 2016) - Chen, Yu-Min; Nguyen, Anh Son; Orazem, Mark E.; Tribollet, Bernard; Pébère, Nadine; Musiani, Marco; Vivier, Vincent
Abstract: The Voigt measurement model, developed in the 1990s for identification of the error structure of impedance measurements, is shown here to have utility in identifying resistivity distributions that give rise to frequency dispersion. The analysis was validated by application to synthetic data derived from a constant–phase–element model, a power–law distribution of resistivity, and an exponential distribution corresponding to a Young impedance. The application to experimental data obtained from coated aluminum demonstrates its utility for interpretation of impedance measurements.